Motives For Fraudulent Behavior In Islamic Bank: Hexagon Model Of Perspective Fraud - Meilany, Merry; Winario, Mohd. (LPPM ISNJ Bengkalis, 2024)
This research explores the motives for fraudulent behaviour using the fraud hexagon model approach in Islamic Bank X, city Y. This research is qualitative research with primary data sources. Data collection was carried out through unstructured interviews and then deepened through observation. The informants for this research consisted of 7 people who had worked and were currently working in several parts of Islamic Bank X, city Y. This research used qualitative data analysis techniques with three stages in the form of data reduction, data presentation and conclusion. This research reveals the motives for fraudulent behaviour at Islamic Bank X in City Y from the perceptive fraud hexagon model. Fraudulent behaviour is based on the perpetrator's intention and is driven by motives in the form of pressure, rationalization, opportunity, ability, arrogance and collusion. Companies can use the results of this research to consider strategies and policies for controlling risks against fraud. The results of this research can also be helpful for Islamic Banks regarding the suitability of a person's position. Sharia banks must develop their human resources well so that there is a balance between employee rights and obligations.